2009
DOI: 10.1021/bm900372x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Cationic Poly(β-hydroxyalkanoate) as a Plasmid DNA Delivery System

Abstract: Poly(β-hydroxyalkanoates) (PHAs) are biodegradable polymers produced by a wide range of bacteria. The structures of these polymers may be tuned by controlling the available carbon source composition, but the range of functional groups accessible in this manner is limited to those that the organism is able to metabolize. Much effort has been made to chemically modify the side chains of these polymers to achieve new materials with new applications. We have previously reported the synthesis of the first cationic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Both properties inform about the electroneutrality ratio in terms of molar charge ratio ( eff = 1) or mass ratio ( / GV NA mm ) between the gene vector (m GV ) and nucleic acid (m NA ) masses. The electrostatic interaction in the complex may be also studied by conductivity [91] or, with less accuracy, by gel electrophoresis [92,93]. Fluorescence intercalation assays with ethidium bromide or GelRed, and circular dichroism have been used for monitoring the DNA compaction process by the gene vector together with the nature of the GV-NA interaction [77,[94][95][96].…”
Section: Biophysical Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both properties inform about the electroneutrality ratio in terms of molar charge ratio ( eff = 1) or mass ratio ( / GV NA mm ) between the gene vector (m GV ) and nucleic acid (m NA ) masses. The electrostatic interaction in the complex may be also studied by conductivity [91] or, with less accuracy, by gel electrophoresis [92,93]. Fluorescence intercalation assays with ethidium bromide or GelRed, and circular dichroism have been used for monitoring the DNA compaction process by the gene vector together with the nature of the GV-NA interaction [77,[94][95][96].…”
Section: Biophysical Methodsmentioning
confidence: 99%
“…(ii) multivalent cationic lipids [67,78,139,178,181], derivated oligoamines [182] and tripeptide multivalent lipids [122]; (iii) cationic polymers derivatives from PEI [124,127,183,184], PAMAM [132,140], PDMAEMA [123,133,185], PAA [103,131,186,187], chitosan [188], polyphosphoramidates [189], polyhydroxyalkanoate [92], polyamines [107], polyaminoacids [127,190] or diblock copolymers [191]; (iv) polycations from calixarene [40,136,165,192] or cyclodextrin [134,135,142,164,193] derivatives; (v) lipopolymers from lysine derivatives [170]; (vi) pendant polymercationic cyclodextrins [129,130,163]; and (vii) cationic polymer-cyclodextrin polyrotaxanes [89]. The picture that results from these transfection studies is that many of the polyplexes show efficacies comparable to that reported by the Lipo2000 positive control and also by most of the commercial or synthezised univalent CLs, but its efficacy as transfecting agents of DNA is still below than that reported by most of t...…”
Section: Biochemistry Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the carrier of hereditary information and involved in the biological synthesis of enzymes and proteins via transcription and replication [1,2]. DNA is most important cellular target for many natural and synthetic organic molecules, especially, anticancer and antiviral drugs [3][4][5]. Binding of small molecules with DNA is very important for designing low-toxic drugs for clinical use [1] because the binding modes and binding properties during the interaction can help us to understand the functional mechanism of drugs and provide theoretical background for the development of new drugs targeted to DNA [3][4][5].…”
Section: Introductionmentioning
confidence: 99%